3
$\begingroup$

I'm given a inequality as such: $n! > n^3$ Where n > 5,

I've done this so far:

BC: n = 6, 6! > 720 (Works)

IH: let n = k, we have that: $k! > k^3$

IS: try n = k+1, (I'm told to only work from one side)

So I have (k+1)!, but I'm not sure where to go from here.

I've been told that writing out: $(k+1)! > (k+1)^3$ is a fallacy, because I can't sub in k+1 into both sides, but rather prove from one side only.

Any Help on how to continue from here, would be much appreciated.

$\endgroup$
2
$\begingroup$

You have $(k+1)!=(k+1)k!>(k+1)k^3$ by the induction hypothesis. Now it suffices to show that if $k>5$ then $k^3 > (k+1)^2$. To do that, we write $(k+1)^2 = k^2 +2k+1 < k^2 + kk + k^2 = 3k^2 < kk^2 = k^3$, since we're assuming $k>5$.

$\endgroup$
2
$\begingroup$

Note that it is equivalent to prove that $n!/n^{3} > 1$ for all $n \geq 6$. You have proved for $n = 6$; suppose $n \geq 6$ is such that $n! > n^{3}$; then $$ \frac{(n+1)!}{(n+1)^{3}} > \frac{n^{3}(n+1)}{(n+1)^{3}} = \frac{n^{3}}{(n+1)^{2}} = \frac{n^{3}}{n^{2}+2n+1} > \frac{n^{3}}{4n^{2}} = \frac{n}{4} > 1. $$ You know how to conclude.

$\endgroup$
2
$\begingroup$

Suppose $n \ge 6$ and $n! > n^3$. You want to show that this implies that $(n+1)! > (n+1)^3 $.

Since $n! > n^3$ and $(n+1)! =(n+1)n! $, we have $(n+1)! > (n+1)n^3 $.

So, we are done if we can show that $(n+1)n^3 \ge (n+1)^3 $.

But, dividing by $n+1$, this is equivalent to $n^3 \ge (n+1)^2 $. There are a variety of ways to prove this - you can even use induction.

Here is a direct way:

Since $n \ge 6$, $(n+1)^2 =n^2(1+\frac1{n})^2 \le n^2(1+\frac1{6})^2 \le n^2\frac{49}{36} < 2n^2 $. But $n^3 \ge 6n^2 > 2n^2 > (n+1)^2 $ and we are done.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.